PENGARUH PEMAHAMAN WAJIB PAJAK, PELAYANAN APARAT PAJAK, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UKM (Studi Kasus UKM di Kecamatan Cepu, Blora Kota dan Banjarejo) - Habib Luthfi Yana, 14.05.52.0170; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
This study aims to empirically examine the effect of taxpayer understanding, service of tax officials and taxation sanctions on UKM taxpayer compliance. The population in this study were UKM taxpayers in Blora Regency as many as 100 UKM in 3 sub-districts namely, Cepu District, Blora City District, and Banjarejo District. The sampling method used is the Convenience Sampling method, which is a sample selection method based on convenience, where this method selects a sample from a population element whose data is easily obtained by the researcher. The results of this study are understanding of taxpayers influencing UKM taxpayer compliance, service of tax officials and taxation sanctions do not affect the compulsory compliance of UKM. Keywords: Taxpayer Comprehension, Tax Apparatus Service, Tax Sanction, UKM Taxpayer Complian